Efektivitas Penggunaan Aplikasi Web Dalam Dunia Pendidikan - Pulung Adi Nugroho; Safuan Safuan (Jurnal Pendidikan Indonesia, 2025)
The rapid development of Information and Communication Technology (ICT) has significantly impacted various sectors, including education. One of the notable digital transformations in education is the use of WEB-based applications for learning, administration, and interaction between educators and students. These technologies offer flexibility, efficiency, and accessibility, enabling educational activities to be conducted anytime and anywhere. This study aims to evaluate the effectiveness of WEB-based platforms in supporting educational activities and to identify the key factors influencing their utilization. A descriptive analysis method was employed in this research, involving a case study of a private school in Tangerang, Banten. The findings reveal that while WEB-based platforms are widely adopted, their effectiveness is still hindered by factors such as infrastructure readiness, the digital literacy of educators and students, and institutional policy support. Key challenges identified include inadequate training for users and limited supporting facilities in some areas. This research highlights the need for better infrastructure and policy support to optimize the use of WEB technology in education.